2018
DOI: 10.21873/invivo.11257
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Urinary Amino Acid Patterns in Individuals with Different Types of Urological Tumor Urinary Amino Acid Patterns as Markers of Urological Tumors

Abstract: Abstract. Background: Insufficient specificity and invasiveness of currently used diagnostic methods raises the need for new markers of urological tumors. The aim of this study was to find a link between the urinary excretion of amino acids and the presence of urological tumors. Materials and Methods: Using ion-exchange chromatography, we tested urine samples of patients with prostate cancer (n=30), urinary bladder cancer (n=28), renal cell carcinoma (n=16) and healthy volunteers (control group; n=21). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Furthermore, our method can detect antigen-antibody complexes which form as a result of immune response under pathological conditions. On the other hand, various factors are reported as disease-specific marker in patients with BC (45,46). Therefore, further studies on the urine levels of our significant BC-related ICantigens are necessary, and the results obtained by such future studies and findings showed by other studies may be important to discuss the diagnostic tools and observation strategies in BC.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, our method can detect antigen-antibody complexes which form as a result of immune response under pathological conditions. On the other hand, various factors are reported as disease-specific marker in patients with BC (45,46). Therefore, further studies on the urine levels of our significant BC-related ICantigens are necessary, and the results obtained by such future studies and findings showed by other studies may be important to discuss the diagnostic tools and observation strategies in BC.…”
Section: Discussionmentioning
confidence: 94%
“…Positive associations of sarcosine or sarcosine metabolism-related proteins with cancer have been observed in pheochromocytoma/paraganglioma 71 , renal cell carcinoma 72 , breast cancer 73 , and particularly in prostate cancer, in which it is considered a potential biomarker 60 , 74 76 . Although sarcosine has not been highlighted by most head and neck cancer studies, it was not surprising to observe high levels of this amino acid in the plasma of our OSCC patients considering that the disease has features of chronic alcohol abuse, starvation state and weight loss.…”
Section: Resultsmentioning
confidence: 99%